The Financial Management Control (F.M.C) - the Managerial Tool for Information and Reporting on the Economic-Financial Activity of the Economic Entity. Application Features (Acta Universitatis Danubius. Œconomica, 2022)
In the present study, the financial management control ( F.M.C ) it is debated from the perspective of the managerial tool for information and reporting on the economic-financial activity of the economic entity, including its application features. Planning issues were covered, the way of exercise, activity reporting to executive and non-executive management and its use of the information provided. Regarding reporting, it was also proposed to develop an easy-to-access application that allows quick information at any time, with increased accuracy generating both consolidated, and individualized on the value of economic-financial deviations, number of constant deficiencies, the stage of their remediation, disciplinary and administrative investigations, sanctions etc., these not being limiting.